First report of Sarcocystis spp. (Apicomplexa, Sarcocystidae) in Lagostomus maximus (Desmarest, 1917) (Rodentia, Chinchillidae) in Argentina - Canova, Victoria (2023)
Sarcocystis is a genus of intracellular parasitic protozoa that infects various species of mammals, birds, and reptiles worldwide. At least 46 Sarcocystis species naturally infect rodents as intermediate hosts producing tissue cysts. This study aimed to provide the first report and molecular characterisation of Sarcocystis spp. in muscles from plains viscacha (Lagostomus maximus) in Argentina. Muscle samples of 53 plains viscachas from three provinces of Argentina were processed by homogenisation and optical microscopy to detect tissue cysts. Positive samples were analysed by PCR-sequencing, using the following markers: 18S rRNA, ITS1, and coxI. The 18S rRNA and coxI consensus sequences were aligned with other sequences from Sarcocystis spp., and phylogenetic trees were constructed. Of all animals processed, 13.2% (7/53) harboured Sarcocystis sp. cysts. 18S rRNA consensus sequences were obtained from four muscle samples and one individual cyst, and they showed 99.88–100% similarity, except for the cyst sequence, which showed 97.11% homology. Similarities of only 96–97% were recorded in the 18S rRNA fragment with other Sarcocystis spp. whose sequences are available in the GenBank. The five coxI fragment sequences obtained were 100% identical and showed an identity of 99.41–99.48% with S. canis. For ITS1 only short and low-quality sequences were obtained. In the phylogenetic trees, all the sequences from plains viscachas were positioned together in a branch separated from other Sarcocystis spp. These results could be related to new Sarcocystis spp. producing sarcocysts in plains viscachas. Besides, comprehensive cyst morphological analysis using TEM from the new Sarcocystis species will allow a description of the cyst wall ultrastructure. In this sense, further studies are needed to deepen these findings and elucidate other potential intermediate and possible definitive hosts.